INNOVATION IN PROCESSING SOY MILK PULP INTO BROWNIES IN MSMES IN RANDEGAN VILLAGE A CASE STUDY AND ITS IMPLICATIONS - Wisaksono, Arief; Tinara , Dinda Tia; Pradana, Aldi; Anjani, Kafita Luluk; Rahmawati, Jurotul Islamiah Nur; Fauziyah, Mai Rizki; Adiansyah, Aldo (Antis-publisher, 2024)
General Background: Soybean dregs, a by-product of soybean juice processing, are typically regarded as waste, despite their nutritional potential. Specific Background: In Randegan Village, local UMKM (Micro, Small, and Medium Enterprises) have begun utilizing soybean dregs to create innovative products, such as brownies, offering a healthier alternative to conventional baked goods. Knowledge Gap: Despite the environmental and economic benefits, limited research has been conducted on the processing techniques, challenges, and broader impacts of using soybean dregs in food production within small-scale industries. Aims: This study aims to explore the innovation process of transforming soybean dregs into brownies, examining the production methods, nutritional benefits, challenges faced by UMKM, and the resulting economic and social impact on the local community. Results: The findings indicate that this innovation not only reduces waste but also increases the value of soybean dregs by converting them into high-nutrition brownies. The initiative has enhanced community empowerment, boosted local income, and decreased unemployment in Randegan. Novelty: This research highlights the transformation of an underutilized waste product into a marketable and health-conscious food product, filling a gap in the literature on sustainable waste utilization in food production. Implications: The study provides practical recommendations for further developing UMKM in rural areas and promotes the adoption of soybean dregs as a resource for local economic growth. Furthermore, it offers insights for policymakers on the benefits of integrating waste-to-product innovations into regional development strategies.